Penghentian Penuntutan Tindak Pidana Penyalahgunaan Narkotika Berdasarkan Keadilan Restoratif Di Kejaksaan Tinggi Jawa Tengah - Elvany, Ayu Izza; Sasikirana, Reswara Padma (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract The development of law enforcement in Indonesia has long recognized the concept of restorative justice. The Attorney General's Guideline Number 18 of 2021 concerning the Resolution of Narcotics Abuse Criminal Cases Through Rehabilitation with a Restorative Justice Approach as the Implementation of the Principle of Dominus Litis by the Prosecutor serves as the legal basis for Public Prosecutors in handling narcotics abuse cases based on restorative justice. This study aims to examine the implementation of the Termination of Prosecution for Narcotics Abuse Crimes Based on Restorative Justice at the Central Java High Prosecutor's Office. The research method used is empirical legal research, employing a sociological approach. Data were collected through interviews, literature review, and document analysis. The results indicate that first, the considerations of the Central Java High Prosecutor's Office in approving proposals from District Prosecutor Offices regarding the termination of prosecution for narcotics abuse crimes based on restorative justice comply with the Attorney General's Guideline Number 18 of 2021 concerning the Resolution of Narcotics Abuse Criminal Cases Through Rehabilitation with a Restorative Justice Approach as the Implementation of the Principle of Dominus Litis by the Prosecutor. Second, although the implementation of the cessation of prosecution for drug abuse offenses has been carried out in accordance with the provisions of the Attorney General's Guidelines Number 18 of 2021, there are obstacles in its implementation related to the financing of rehabilitation for drug abuse, which is required to be funded by the State.